2016
DOI: 10.1103/physrevb.94.085125
|View full text |Cite
|
Sign up to set email alerts
|

Excitation spectra of aromatic molecules within a real-spaceGW-BSE formalism: Role of self-consistency and vertex corrections

Abstract: We present first-principle calculations on the vertical ionization potentials (IPs), electron affinities (EAs), and singlet excitation energies on an aromatic-molecule test set (benzene, thiophene, 1,2,5-thiadiazole, naphthalene, benzothiazole, and tetrathiafulvalene) within the GW and BetheSalpeter equation (BSE) formalisms. Our computational framework, which employs a real-space basis for ground-state and a transition-space basis for excited-state calculations, is well-suited for high-accuracy calculations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 93 publications
2
60
1
Order By: Relevance
“…where Z (ω) is given by Eq. (19). In a weakly or moderately correlated regime, one can clearly distinguish dominant quasiparticle peaks from satellites, whereas this scenario can break down in the strongly correlated regime.…”
Section: B Self-consistent Gwmentioning
confidence: 96%
“…where Z (ω) is given by Eq. (19). In a weakly or moderately correlated regime, one can clearly distinguish dominant quasiparticle peaks from satellites, whereas this scenario can break down in the strongly correlated regime.…”
Section: B Self-consistent Gwmentioning
confidence: 96%
“…28,119 PBE+TS used here, has provided reliable predictions for the structure of PAH crystals, 27,75,[120][121][122] however somewhat larger deviations from experiment are obtained for HB perylene, as discussed in the SI. Errors in the G 0 W 0 step may stem from the G 0 W 0 approximation itself (i.e., neglecting the vertex, lack of selfconsistency, and the diagonal approximation), [123][124][125][126][127][128] numerical settings, pseudopotentials, 129,130 the mean-field starting point (e.g., self-interaction errors in DFT functionals), 111,[131][132][133] and approximations used in the self-energy evaluation, such as the Hybertsen-Louie generalized plasmon-pole model. 89 GW+BSE only considers particlehole interactions and cannot describe states with multi-exciton character 134,135 (it has been postulated based on multi-reference calculations that one of the low-lying excitons of the quaterrylene molecule in the gas phase may have a fraction of double-excitation character, 136,137 however such calculations cannot be performed for molecular crystals with periodic boundary conditions).…”
Section: Electronic and Optical Properties Of Perylene And Quaterrylenementioning
confidence: 99%
“…42 Several recent benchmarks for molecular systems, using different codes, have shown that G 0 W 0 +BSE@PBE systematically underestimates both singlet and triplet excitation energies. 123,[112][113][114] It is presently unknown whether the same trends persist in molecular solids, in part owing to lack of high-level reference data for periodic systems. From here on, we restrict the discussion to qualitative trends.…”
Section: Electronic and Optical Properties Of Perylene And Quaterrylenementioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] It now stands as a cost-effective computational method that can model excited states 22,23 with a typical error of 0.1-0.3 eV for spin-conserving transitions according to large and systematic benchmarks. [24][25][26][27][28][29][30] One of the main advantages of BSE compared to TD-DFT is that it allows a faithful description of charge-transfer states. [31][32][33][34][35][36] Moreover, when performed on top of a (partially) self-consistent evGW calculation, [37][38][39][40][41][42][43] BSE@evGW has been shown to be weakly dependent on its starting point (e.g., on the exchange-correlation functional selected for the underlying DFT calculation).…”
mentioning
confidence: 99%